Modulations in gastrointestinal microbiota during postpartum period fulfill energy requirements and maintain health of lactating Tibetan cattle - Liu, Jing; Ahmad, Anum Ali; Yang, Chen; Zhang, Jianbo; Zheng, Juanshan; Liang, Zeyi; Wang, Fang; Zhai, Huan; Qin, Shuanghong; Yang, Feng; Ding, Xuezhi (Frontiers in Microbiology, 2024)
Postpartum period of dairy cattle is an important phase of their life mainly associated with the changes in physiology, rumen function, and energy metabolism. Studies have shown that gut microbial composition undergoes drastic changes during the postpartum period. However, little is known about the temporal variations in digestive tract microbiota in postpartum Tibetan cattle. The aim of this study was to investigate the temporal variations in blood metabolites, ruminal fermentation, and microbial community of oral, rumen, and gut in lactating Tibetan cattle during postpartum. We collected blood, saliva, rumen fluid, and fecal samples from lactating Tibetan cattle during first week (1W), the second week (2W), the first month (1M) and the second month (2M) of the postpartum period. The microbiota of saliva, rumen fluid, and fecal samples were assessed using 16S rRNA sequencing. The rumen volatile fatty acid and blood parameters were also quantified. The content of volatile fatty acids (VFAs) and blood parameters showed opposite tendency to each other and reached to stability at 2M. Rumen microbiota showed the highest alpha diversity compared to other two sites. At phylum level, the oral cavity was dominated by Proteobacteria, while most dominant phylum in rumen and feces were Firmicutes and Bacteroidetes, respectively. The dominant genera in oral cavity were Moraxella and Bibersteinia, while genera Prevotella 1 and Ruminococcaceae UCG-005 were dominant in rumen and fecal samples, respectively. Microbial network analysis revealed that most of the active genera in all networks belonged to phylum Firmicutes, indicating the importance of this phyla during postpartum period of lactating cattle. The functional analysis revealed distinct division of labor among three gastrointestinal sites associated with defense, fatty acid synthesis, and maintaining health of host. All in all, our findings provide insights into the metabolic and microbial changes of lactating Tibetan cattle and help to the improvement of the management strategies.